Effect of fiber orientation on tensile behavior of biocomposites prepared from nettle and poly(lactic acid) fibers: Modeling & experiment. (1st April 2018) - Kumar, Navdeep; Das, Dipayan; Neckář, Bohuslav
Abstract: In this work, a micromechanical model of tensile behavior of fibrous composites was formulated by taking into account of the stress-strain behavior of fiber and matrix, the directional arrangement of fibers in the composites, and the relative space occupied by the constituent fibers and matrix in the composites. A simple and easy-to-use expression was obtained for predicting the tensile stress of composites as a function of tensile stresses of fiber and matrix, fiber and matrix volume fractions, and fiber orientation factor. The model was validated with a set of biocomposites prepared by using nettle and poly(lactic acid) fibers and employing compression moudling technology. The model was also compared with the well-known "rule of mixtures" equation using the experimental results. While the "rule of mixtures" equation was found to highly overestimate the tensile stress, the model predicted the experimental results satisfactorily.